ANALISIS PENGARUH PERANAN GEMBALA DALAM PELAYANAN KONSELING PRA-NIKAH UNTUK KEHARMONISAN KELUARGA DI JEMAAT GEREJA MASEHI ADVENT HARI KETUJUH KONFERENS DKI JAKARTA WILAYAH EMPAT BERDASARKAN EFESUS 5:22-25 - Situmeang, Berlin; Peranginangin, Joseph (Jurnal Marturia, 2017)
An Analysis of the influence of the shepherd's role in pre-marriage counseling services for family harmony in the Seventday Adventist church at the fourth regional Jakarta local conference based on Ephesians 5:22-25. Keywords: The concept of marriage, Role of Shepherd, Counseling, and example. The discussion of pre-marriage counseling under Ephesians 5: 22-25 is highly relevant today, given that the institution of marriage has been established by God since the time of Eden before any institutions exist anywhere on the planet. Marriage is God's ordinance, God says, "it is not good that man should be alone" (Genesis 2:18), while in the past there are many marriages that have eventually found a dead end and destruction, these marriages have gone into the realm of the children's lives, sons of God. A marriage is suppose to be a unity of loving commitment to be manifested as a little paradise in the world, that has become corrupted and bitter. Satan desperately wants to destroy the marriage from the beginning and now it is a demonic attempt to mar the marriage. Where the commitment of love fades, loyalty disappears and is replaced by infidelity, as well as the bitter roots that appear in the dynamics of marrying. The concept of marriage is increasingly obscured by the emergence of polygamy in which a husband is married more than one wife. Polyandry is a wife married more than one Husband, LGBT is lesbian (female love fellow woman), gay or homo, bisexual that is loving the opposite sex and can love same-sex and transgender. A marriage contracts is where the contract is only the age of the agreed commitment and not of a lifetime contract. The role of the shepherd is very important to restore a biblical marriage and prepare the children of God to be ready to enter into a happy marriage that is not easily shaker by issues or problems. A study was conducted in the Seventh-day Adventist Church of the Fourth Area Jakarta Local Conference with a view of knowing how strongly the influence of the Shepherd's role for the pre-marriage counseling is. To what extent the church members' understanding the true biblical marriage concept that is specifically based on Ephesians 5: 22-25 , How important is the role of shepherd in providing pre-marital counseling for married couples, and the extent to which exemplary influence is good for the next generation. The method used in this research is quantitative research, and data collection tools used in the form of questionnaires to measure the variable influence of the role of the shepherds in Pre-marital counseling based on Ephesians 5: 22-25. The results showed that first, the respondent understands that the institution of marriage was founded by God since the Garden of Eden, That the marriage is holy and marriage is very necessary to be prepared for carefully, so that is the understanding of the real concept of marriage for couples who are getting married. Secondly, respondents strongly believe that it is very important to have briefing through pre-marital counseling services for married couples therefore this is the role of shepherds to provide for the pre-marital counseling for married couples. Thirdly, respondents strongly agree that they accepted their partners completely, both their strengths and weaknesses, and this is the best example of how they will influence in a marriage. The final part are the conclusion of the analysis of field research and suggestions of applications that can be executed to return the actual marriage designed by God, and blessed and become a blessing.